Evolutionary economic thought : European contributions and concepts (Cheltenham : Edward Elgar Publishing, 2003)
This book explores the theoretical roots of the evolution approach. It focuses on establishing a history of evolutionary economic thought.
Includes bibliographical references and index.
aia 17/09/13; osa 20/11/13
Loan
Keywords: Evolutionary economics; Evolutionary economics -- Europe